2015 IEEE 35th International Conference on Electronics and Nanotechnology (ELNANO) 2015
DOI: 10.1109/elnano.2015.7146918
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a handshake between humans using wavelet transforms

Abstract: Physical and social interaction between humans and robots are important for humanoid robotics. In this paper the physical characteristics of handshakes between humans are deeply analyzed using the wavelet transforms to reproduce future experiments of handshakes between a human and a robot. A special pair of data gloves has been designed to measure acceleration patterns of human arms during handshakes. Most energy of an acceleration signal reached by wavelet coefficients is concentrated within the time range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A group of researchers from the University of Lorraine, France explicitly study the mutual synchronisation (MS in short) between participants while shaking hands along with the forces exerted on the palms [45,[47][48][49]79]. They firstly study the hand motions by having the participants wear a glove with an Inertial Measurement Unit (IMU) and 6 force sensors placed around the palm [48].…”
Section: Insights From Human-human Handshake Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of researchers from the University of Lorraine, France explicitly study the mutual synchronisation (MS in short) between participants while shaking hands along with the forces exerted on the palms [45,[47][48][49]79]. They firstly study the hand motions by having the participants wear a glove with an Inertial Measurement Unit (IMU) and 6 force sensors placed around the palm [48].…”
Section: Insights From Human-human Handshake Interactionsmentioning
confidence: 99%
“…The MS between participants is analysed using the Fourier analysis of the input signals (mainly accelerations). However, wavelet transforms are shown to qualitatively estimate the different stages of a handshake interaction as well [49].…”
Section: Insights From Human-human Handshake Interactionsmentioning
confidence: 99%
“…Human-human handshake analysis: In [9], a conceptual framework for handshaking between humans and robots is presented, which divides the handshake into three stages: hand reaching, hand gripping and shaking and synchronization, emphasizing the fact that each part of the movement at various stages needs to be more human-like for a more realistic perception. Another study [11] utilizes wavelet transformation to thoroughly evaluate the physical properties of a handshake, such as the acceleration of the human arm. It was found that the handshaking phases in [9] can be described qualitatively using wavelet scalogram analysis.…”
Section: Related Workmentioning
confidence: 99%
“…A group of researchers from the University of Lorraine, France explicitly study the mutual synchronisation (MS in short) between participants while shaking hands along with the forces exerted on the palms [45,47,48,49,75]. They firstly study the hand motions by having the participants wear a glove with an Intertial Measurement Unit (IMU) and 6 force sensors placed around the palm [48].…”
Section: Insights From Human-human Handshake Interactionsmentioning
confidence: 99%